Computational imaging from non-uniform degradation of staggered TDI thermal infrared imager - Sun,T; Liu,JG; Shi,Y; Chen,W; Qin,Q; Zhang,Z (Optics Express, 2015)
For the Time Delay Integration (TDI) staggered line-scanningthermal infrared imager, a Computational Imaging (CI) approach isdeveloped to achieve higher spatial resolution images. After a thoroughanalysis of the causes of non-uniform image displacement and degradationfor multi-channel staggered TDI arrays, the study aims to approach onedimensional(1D) sub-pixel displacement estimation and superposition ofimages from time-division multiplexing scanning lines. Under theassumption that a thermal image is 2D piecewise C2 smooth, a sparse-andsmoothdeconvolution algorithm with L1-norm regularization termscombining the first and second order derivative operators is proposed torestore high frequency components and to suppress aliasing simultaneously.It is theoretically and experimentally demonstrated, with simulation andairborne thermal infrared images, that this is a state-of-the-art practical CImethod to reconstruct clear images with higher frequency components fromraw thermal images that are subject to instantaneous distortion and blurring.